Information Disorder: Toward an Interdisciplinary Framework for Research and Policy Making - Kai-nunna, Phirakan (Journal of Information and Learning [JIL], 2024)
In today’s world, issues arise pertaining to not only information overload but also an abundance of inaccurate information circulating in the communication field, which is difficult to verify for ordinary users. Various types of information are also employed as political tools that are generated, disseminated, and amplified either mis- or dis-information across borders using artificial intelligence. This situation is called information pollution. This phenomenon has been studied and presented in the report of Information disorder: Toward an interdisciplinary framework for research and policy making. The report consists of information disorder, the problem of filter bubbles and echo chambers, phrases and elements of information disorder, interesting case studies, and policy recommendations for different institutions. In addition, the critique of the content from this report is namely, as follows: difficulties for online media consumers in recognizing various types of information disorder, inequality between English-speaking and non-English-speaking nations, benefits gained by platform owners from user engagement in information disorder, and ideological domination.